KAJIAN PUSAT PERTUMBUHAN KABUPATEN LANGKAT - Hutapea, Lewi (Jurnal Samudra Geografi, 2025)
This research provides an important insight into the development imbalance in Langkat Regency, which is caused by the concentration of facilities and infrastructure in Stabat District. Using three analytical approaches—Centrality Index, König and Shimbel Connectivity, and Gravity Analysis—the study successfully identifies other districts with potential as growth centers that can help reduce this imbalance. The results of the study show that the development of more than one growth center, such as Stabat District as the primary center and Tanjung Pura and Bohorok Districts as secondary growth centers, can create a balance between the central, southern, eastern, and western regions of Langkat Regency. With the establishment of more evenly distributed growth centers, it is expected that facilities and infrastructure access can be more evenly distributed to hinterland areas, which previously had limited access. This approach also provides a strong foundation for more inclusive and equitable development planning, taking into account the interconnectedness of regions that can support each other in economic interactions and public services. Thus, this study serves as an important reference for designing development strategies that are more just for all districts in Langkat Regency.